Tailor‐Made Photoconductive Pyrene‐Based Covalent Organic Frameworks for Visible‐Light Driven Hydrogen Generation. Issue 24 (28th June 2018) - Stegbauer, Linus; Zech, Sebastian; Savasci, Gökcen; Banerjee, Tanmay; Podjaski, Filip; Schwinghammer, Katharina; Ochsenfeld, Christian; Lotsch, Bettina V.
Abstract: Covalent organic frameworks (COFs) have emerged as a new class of crystalline porous polymers displaying molecular tunability combined with structural definition. Here, a series of three conjugated, photoactive azine‐linked COFs based on pyrene building blocks which differ in the number of nitrogen atoms in the peripheral aromatic units is presented. The structure of the COFs is analyzed by combined experimental and computational physisorption as well as quantum‐chemical calculations, which suggest a slipped‐stacked arrangement of the 2D layers. Photocurrents of up to 6 µA cm −2 with subsecond photoresponse times are measured on thin film samples for the first time. While all COFs are capable of producing hydrogen from water, their efficiency increases significantly with decreasing number of nitrogen atoms. The trending activities are rationalized by photoelectrochemical measurements and quantum‐chemical calculations which suggest an increase in the thermodynamic driving force with decreasing nitrogen content to be the origin of the observed differences in hydrogen evolution activities. Abstract : A series of three conjugated pyrene‐based azine‐linked covalent organic frameworks (COFs) which differ in the number of nitrogen atoms in the peripheral aromatic units is presented. All COFs are photoactive and produce photocurrents up to 6 µA cm −2 as thin films. The decreasing hydrogen evolution activity with decreasing nitrogen content points to an oxidative quenching mechanism.